Determination of Carbamazepine and its Active Metabolite Epoxycarbamazepine from Plasma by Liquid Chromatography-Mass Spectrometry - R. More, Abhijit; Vaidya, A.J.; Vaidya, Vikas; Deshmukh, R.G. (Asian Journal of Chemistry, 2016)
High performance liquid chromatography-mass spectrometry method is described for the determination of carbamazepine and epoxycarbamazepine in human plasma using fluconazole as internal standard. Good separation of the target compounds and short run time were obtained using an elution system of methanol : water (90 : 10% v/v). Carbamazepine and epoxycarbamazepine were isolated by solvent extraction. No significant interference caused by endogenous compounds was observed. This simple and rapid assay can be successfully used in pharmacokinetic studies of carbamazepine and epoxycarbamazepine.